Quantitative measurement of transthyretin mistargeting by proximity labeling and parallel reaction monitoring - Lyu, Ziqi; Genereux, Joseph C. (Frontiers in Chemical Biology, 2023)
Proximity labeling is a powerful approach for characterizing subcellular proteomes. We recently demonstrated that proximity labeling can be used to identify mistrafficking of secretory proteins, such as occurs during pre-emptive quality control (pre-QC) following endoplasmic reticulum (ER) stress. This assay depends on protein quantification by immunoblotting and densitometry, which sometimes suffers from poor sensitivity. Here, we integrate parallel reaction monitoring (PRM) mass spectrometry to enable a more quantitative platform, and assess how chemical ER stressors impact pre-QC of the model secretory protein transthyretin in HEK293T cells. We find that some drug treatments affect labeling efficiency, which can be controlled for by normalizing to APEX2 auto-labeling. While some chemical ER stress inducers including Brefeldin A and thapsigargin induce pre-QC, tunicamycin and dithiothreitol do not, indicating ER stress alone is not sufficient. This finding contrasts with the canonical model of pre-QC induction, and establishes the utility of our platform.